Comparison of Publication Rates for Musculoskeletal Oncology Abstracts Presented at National Meetings. (8th March 2021) - Collier, Christopher D.; Quereshy, Humzah A.; Getty, Patrick J.
Abstract : Background . Scientific meetings provide a forum to disseminate new research and advance patient care. The American Academy of Orthopaedic Surgeons (AAOS), Connective Tissue Oncology Society (CTOS), and Musculoskeletal Tumor Society (MSTS) annual meetings are examples of such gatherings in the field of musculoskeletal oncology. After a review of select MSTS abstracts from 1991 to 1999 revealed a 41% publication rate in scientific journals, previous authors cautioned meeting attendees that the majority of abstracts may not survive rigorous peer review and may not be scientifically valid. Since two decades have passed, this study reexamined publication rates and characteristics in a contemporary and expanded cohort of oncology abstracts presented at the AAOS, CTOS, and MSTS annual meetings. Methods . 1408 podium and poster abstracts from the AAOS (oncology-focused from 2013 to 2015), CTOS (2012 to 2014), and MSTS (2012 to 2014) annual meetings were reviewed to allow for a four-year publication window. Searches were performed with PubMed and Google Scholar databases to identify full-text publications using abstract keywords. Characteristics of each abstract and resulting publication were collected. Statistical analysis was performed using the chi-square and Kruskal-Wallis tests for time-independent comparisons, and the log-rank test after reverse Kaplan-Meier analysis for time-dependent comparisons. Results . Abstract publication rates overall were higher for podium presentations (67%, 280 of 415) compared to poster presentations (53%, 530 of 993; p < 0.001 ). When both abstract types were combined, differences between meetings did not meet statistical significance (AAOS: 65%, 106 of 162; CTOS: 57%, 521 of 909; MSTS: 54%, 183 of 337, p = 0.06 ). Abstracts from AAOS meetings were more often published prior to the first day of the meeting (AAOS: 24%, 25 of 106; CTOS: 10%, 52 of 521; MSTS: 14%, 25 of 183; p < 0.01 ). After excluding previously published abstracts, AAOS abstracts had the shortest time to publication (median: 10.8 months, interquartile range (IQR): 4.4 to 18.8 months), compared to those from CTOS (16.0 months, 8.4 to 25.9 months, p < 0.01 ) and MSTS (15 months, 7.9 to 25.0 months, p < 0.01 ) meetings. CTOS abstracts were published in higher impact journals (median: 3.7, IQR: 2.9 to 5.9), compared to those from AAOS (2.9, 1.9 to 3.2, p < 0.01 ) and MSTS (3.1, 2.3 to 3.1, p < 0.01 ) meetings. Finally, 7.7% (62 of 810) of published abstracts were presented at more than one meeting. Conclusions . Publication rates in this study were higher than previous reports in musculoskeletal oncology and comparable or better than recent reports for other orthopedic meetings. Comparisons across the AAOS, CTOS, and MSTS annual meetings highlight notable differences but suggest similarity overall in the quality of evidence presented with little overlap between meetings. Taken together, this study points to progress in the review processes used by the program committees, reaffirms the importance of critical appraisal when considering abstract findings, and supports the continued organization of multiple scientific meetings in musculoskeletal oncology.